Risk factors for delirium among older adults in the emergency department: a systematic review protocol - Lucas Oliveira J e Silva; Michelle J Berning; Jessica A Stanich; Danielle J Gerberi; Jin Han; Fernanda Bellolio (BMJ Open)
Introduction Delirium is commonly missed in older adults presenting to the emergency department (ED). Although current recommendations for active screening of delirium in the ED, this might not be feasible or practical. Identifying patients at high risk for prevalent and incident delirium in the ED will help to improve the screening process and to build interventions. There is currently scattered synthesis of evidence on risk factors associated with delirium in the ED. To address this gap, we are conducting a systematic review to describe the risk factors (patient vulnerability factors and precipitating factors) for delirium in the ED.Methods and analysis A literature search was performed from inception to March 2020 in Ovid EBM Reviews, Ovid EMBASE, Ovid MEDLINE, Scopus and Web of Science. We will include original research studies that report a quantitative relationship between at least one risk factor and delirium in the ED setting. Two investigators will use eligibility criteria from this protocol to independently screen titles and abstracts, and select studies based on full-text review of potentially eligible studies. After arriving at a final set of included studies, two investigators will extract data using a standardised data collection form. If appropriate, data regarding each risk factor will be pooled through a random-effect meta-analysis. The Grading of Recommendations Assessment, Development and Evaluation approach will be used to evaluate the overall quality of evidence.Ethics and dissemination To our knowledge, this will be the first systematic review evaluating risk factors for prevalent and incident delirium specifically related to the ED setting. Results of this study will aid in the identification of older adults at risk for delirium in the ED. We aim to publish the results of this systematic review in a peer-reviewed journal with good visibility for the fields of emergency medicine and geriatrics.PROSPERO registration numberCDR42020175261